A Research into the Legal and Judicial Principles of the Executed Person Coming Back to Life - Ã˜Â¹Ã˜Â§Ã˜Â¨Ã˜Â¯Ã›ÂŒ Ã˜Â³Ã˜Â± Ã˜Â¢Ã˜Â³Ã›ÂŒÃ˜Â§, Ã˜Â¹Ã™Â„Ã›ÂŒÃ˜Â±Ã˜Â¶Ã˜Â§; Ã˜Â¹Ã™Â„Ã™ÂˆÃ›ÂŒ, Ã˜Â«Ã™Â…Ã˜Â§Ã™Â†Ã™Â‡ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Article 438 of the Islamic penal law considers as renewable the sentence of the executed person coming back to life in case of qiá¹£Äá¹£ (retaliated punishment) due to observance of the resemblance (mumÄthilat) condition and in case demanded by the claimant of blood, but it has kept silent concerning the legal and discretionary punishments like those administered for drugs crimes. The present article, while presenting the viewpoints and critical review of the arguments of the proponents and opponents of renewal of death warrant, tries to answer the main question brought up in this discussion as to whether or not according to the legislator there is a difference between capital punishment, which is regularly intended as death or loss of life, and the concept of disclaiming of life or death. Finally the chosen view will be that in case we believe that execution, like crucifixion (á¹£alb), is typical (qasÄ«m) of murder and the typical of an object cannot be the very object itself, then the above-mentioned verdict can be generalized to execution and suspend the re- execution verdict in legal punishments and penalties, except in premeditated instances.